Understanding Sexual Harassment in the #MeToo Era - Julios, Christina (Sexual Harassment in the UK Parliament: Lessons from the #MeToo Era, 2022)
This chapter provides a contextual account of the rise of #MeToo as an global gender-equality campaign supporting those affected by sexual transgressions. Originally articulated by African-American civil rights activist Tarana Burke in 2006, the slogan ‘me too’ was meant as a rallying cry to support young minority ethic survivors of sexual abuse. Years later, social media would turn Burke’s motto into a byword for the global #MeToo movement. The chapter chronicles the events surrounding #MeToo’s inception, including Hollywood producer Harvey Weinstein’s sexual exploitation scandal in 2017, and The New York Times and The New Yorker exposés of his serial offending within the film industry. It also examines the narratives of countless survivors and #MeToo campaigners, including high-profile cases such as those of Rose McGowan, Alyssa Milano, Mimi Haleyi, Jessica Mann and Zelda Perkins. The chapter then critically considers the growth and international significance of #MeToo as well as its inherent shortcomings.
Keywords: #MeToo; Farrow; Harvey Weinstein; Irina; Kantor and Twohey; Rose McGowan

Sex and safety on set: intimacy coordinators in television drama and film in the VOD and post-Weinstein era - Sørensen, Inge Ejbye (Feminist Media Studies, 2022)
This article examines the work of intimacy coordinators on television drama and film sets and the rise of this new role in the screen industry from a policy and production studies perspective. Since HBO made the employment of an intimacy coordinator mandatory on all productions with scenes of sex, nudity, and physical intimacy in 2018, intimacy coordination has become an industry standard and expectation. Through interviews and analysis of production practices, this article explores how intimacy coordinators change and challenge established production practices on and off set and interrogates the reasons behind the emergence of this role in the screen industry. It situates intimacy coordination in the context of recent industry policies and initiatives that promote equality and diversity, and counter harassment and abuse in the post-Weinstein era. It analyses this role on relation to changing production and distribution models and regimes in the era of VOD portals. The article argues that intimacy coordination is not only a catalyst for reforming practices on set, but a way for the screen industry to negotiate contemporary and historic concerns about sexual harassment and abuse, comply with recent policy and funding requirements, and a mechanism for mitigating economic and reputational risk to productions.
Keywords: #MeToo; Intimacy Coordination; Irina; Prévention; VOD; equality; screen industries